Personality disorders in geriatric inpatients in a tertiary hospital. (October 2014) - Jeyasingam, Neil; Jacob, Kuruthukulangara S; Brodaty, Henry
Objective: To assess the prevalence of personality disorders in general medical geriatric admissions. Methods: Forty of 508 general medical geriatric admissions screened at a large tertiary hospital, who were eligible as defined by a Mini-Mental State Examination score of over 23 and capable of informed consent, were assessed by direct interview and discussion with the patient's family or close contact to determine personality traits. Results: Eight (20%) of these patients were found to satisfy DSM-IV criteria for a personality disorder. They were found to have significantly lower global assessments of functioning, impaired overall functioning and lower quality of life compared with non-personality disordered patients. None of their personality disorders had been recognised by their treating teams. Conclusions: This study supports the need for systematic research into the area and the need for increased clinical awareness of the issues.